2019
DOI: 10.1002/joc.6309
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Atlantic Multidecadal Oscillation precondition in the teleconnection of different El Niño‐Southern Oscillation types and impacts on the 15°N–15°S South American sector precipitation

Abstract: The Eastern Pacific (EP) and Central Pacific (CP) El Niño‐Southern Oscillation (ENSO) types and their impacts on the tropical North Atlantic (TNA) SST variability and 15°N–15°S South American precipitation during the warm and cold phases of the Atlantic Multidecadal Oscillation (WAMO and CAMO) were evaluated during the 1901–2012 period. The results show more frequent ENSO events during the CAMO. The El Niño (EN) (La Niña [LN]) events, regardless of type (EP or CP), during the WAMO (CAMO) were accompanied by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, according to Wu et al (2019), a strong EN before an LN induces warming in the tropical Atlantic and Indian Oceans, delaying the adjustment of these oceans to the LN cooling; and the warming in the tropical Atlantic intensifies the interbasin gradient between this ocean and the eastern tropical Pacific. Since the ENSO teleconnection in the tropical Atlantic is a determinant of the precipitation variability in northeastern Brazil (Andreoli and Kayano, 2006;Figliuolo et al, 2020), the multiyear LN events preceded or not by EN might lead to distinct teleconnection over SA. Here we documented the physical mechanisms associated with a multiyear LN during its Y1 and Y2, which cause distinct seasonal precipitation anomaly patterns in SA.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Wu et al (2019), a strong EN before an LN induces warming in the tropical Atlantic and Indian Oceans, delaying the adjustment of these oceans to the LN cooling; and the warming in the tropical Atlantic intensifies the interbasin gradient between this ocean and the eastern tropical Pacific. Since the ENSO teleconnection in the tropical Atlantic is a determinant of the precipitation variability in northeastern Brazil (Andreoli and Kayano, 2006;Figliuolo et al, 2020), the multiyear LN events preceded or not by EN might lead to distinct teleconnection over SA. Here we documented the physical mechanisms associated with a multiyear LN during its Y1 and Y2, which cause distinct seasonal precipitation anomaly patterns in SA.…”
Section: Discussionmentioning
confidence: 99%
“…Kayano and Capistrano 119 show that El Niño (La Niña) events are stronger during the cold (warm) phase of the AMO due to the anomalous Walker cell to be reinforced by El Niño (La Niña), as a consequence of the negative (positive) SST gradient between the eastern equatorial Pacific and the equatorial Atlantic. According to Figliuolo et al, 120 the anomalous Walker cell shows sinking (ascending) motions and increased (decreased) sealevel pressure in the equatorial and southern parts of the tropical Atlantic, increasing the Pacific-Atlantic inter-basin zonal SST gradient during El Niño and the cold phase of the AMO. Figliuolo et al 120 also evaluated the concomitant impact of the different ENSO (Eastern Pacific and Modoki El Niño and La Niña) episodes and the AMO (warm and cold) on South American precipitation; some of their results include: (1) Eastern Pacific El Niño (canonical events) and the warm phase of the AMO are associated with the intensification of negative precipitation anomalies in northeastern Brazil, since the ITCZ is northward of its position; (2) Eastern Pacific El Niño and the cold phase of the AMO are associated with the intensification of negative precipitation anomalies in the central part of the Amazon caused by the anomalous sinking branch of the Walker cell; (C) Modoki El Niño show a more variable signal (see Figliuolo et al 120 for more details); and (4) Eastern Pacific and Modoki La Niña events, together with the warm phase of the AMO, contribute to negative anomalies in northeastern Brazil.…”
Section: Relationship Between the Amo And The Ensomentioning
confidence: 96%
“…The AMO also modulates precipitation over South America and its teleconnections with ENSO (Kayano and Capistrano, 2014;Flantua et al, 2016;Grimm et al, 2016;Barichivich et al, 2018;Figliuolo et al, 2020). Flantua et al (2016) found a negative correlation between AMO and annual precipitation in the western Cordillera of the southern Peruvian Andes.…”
Section: Introductionmentioning
confidence: 98%
“…The two phases of the AMO result in different patterns of austral summer precipitation anomalies, depending on the phases of the central and eastern ENSO indices between 15 °N and 15 °S (Figliuolo et al, 2020). For example, the eastern Pacific El Niño enhances (reduces) DJF precipitation over the central Peruvian Andes during the warm (cold) AMO phase.…”
Section: Introductionmentioning
confidence: 99%